Are Immigrants Graded Worse in Primary and Secondary Education? – Evidence for German Schools - David Kiss (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Using PIRLS 2001 and PISA 2003 data for Germany, this paper examines whether immigrants attending primary and secondary school are graded worse in math than comparable natives. Controlling for differences in math skills, class fixed effects regressions and results of a matching approach suggest that immigrants have grade disadvantages in primary education. In Germany, track choice after primary education is mainly determined by the average of grades obtained in math and German. Hence, grade disadvantages could lead to lower level track choice. Immigrants who attend the most common secondary school tracks are not graded differently from natives. – – Die vorliegende Studie geht der Frage nach, ob Kinder mit Migrationshintergrund im Fach Mathematik schlechter als vergleichbare einheimische Kinder benotet werden. Im Mittelpunkt stehen hierbei die Primarstufe sowie die weiterführenden Schulformen Gymnasium, Realschule und Hauptschule. Die Auswertung von IGLU 2001 und PISA 2003 Daten ergibt, dass Migranten zweiter Generation in der Grundschule systematisch schlechter als einheimische Kinder benotet werden, selbst wenn Unterschiede in den Mathematikkompetenzen sowie Einflüsse auf Klassenebene heraus gerechnet werden. Hinsichtlich der weiterführenden Schulformen gibt es keine Evidenz, dass Migranten und einheimische Kinder unterschiedlich benotet werden.
Keywords: C40; I21; J15; 330; grading; educational system; migration background; matching